Kashmir Merino The pride of Kashmir - Rather, Mubashir Ali; Alam, Safeer; Khan, Nusrat Nabi; Hamadani, Ambreen (Indian Farming, 2021)
It is concluded from the study that sheep farming in Budgam is mainly practiced by poor, middle aged, male and illiterate people having marginal land holdings and low income with agriculture as main occupation and sheep as secondary source of income. The Kashmir Merino is a variable breed adopted to harsh climate of Kashmir Valley.